49.4k views
2 votes
Can you please help me on 4(-4+m)=-6(m-4)

User Mazdak
by
4.4k points

2 Answers

2 votes

Answer:

m = 4

Explanation:

Given

4(- 4 + m) = 6(m - 4) ← distribute parenthesis on both sides

- 16 + 4m = 6m - 24 ( subtract 6m from both sides )

- 16 - 2m = - 24 ( add 16 to both sides )

- 2m = - 8 ( divide both sides by - 2 )

m = 4

User Qezt
by
5.1k points
2 votes

Answer:

Explanation:

4(-4+m)=-6(m-4)

-16-m=-6m+24

-16=-5m+24

-40=-5m

/-5 = /-5

m=8

User Amaslenn
by
4.5k points